PENGEMBANGAN VIDEO ANIMASI BERBASIS WEB PADA MATA PELAJARAN BAHASA INDONESIA KELAS XI UPT SMA NEGERI 10 SIDENRENG RAPPANG (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop web-based animated videos using the Animaker platform as a learning medium for the Indonesian Language subject for grade XI at the UPT of SMA Negeri 10 Sidenreng Rappang. The approach used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). These stages include needs analysis, storyboard and flowchart design, video production, and validation by material and media experts. The trial was conducted in three stages, namely individual trials, small group trials, and field trials on students. The results of the study showed that the developed animated video media was declared valid by material and media experts, practical for use by teachers and students, and effective in improving student learning outcomes. This video is designed to be flexibly accessible through digital devices such as smartphones and laptops. By using Animaker-based animated video media, learning becomes more interesting, interactive, and able to increase students' motivation and understanding of Indonesian Language material.